KONSEP ‘ASHABIYAH DALAM PEMIKIRAN POLITIK IBNU KHALDUN - Ilham, Muh. (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2016)
‘Ashabiya theory is one proof of how rigor and smart Ibn Khaldun is in analyzing the issue of both politics and state, wherein ‘ashabiya is the key issue of the establishment and the formation of a state. Conversely, when the nature of ‘ashabiya of a state get weaken, the state is subsequently in the brink of its fall. Until recently, the theory proved to be true and that of ‘ashabiya has inspired the emerging contemporary political movement.